Membangun Pemberdayaan Masyarakat yang Berkembang dan Maju Melalui Pelatihan Pembukuan Keuangan UMKM di Desa Srimukti - Elia Rossa; Imas Mutikartini Putri; Nanditya Andini; Sindy Septiani; Eva Yanis Lafione; Aisyah Sekar Ningrum; Arinda Dwi Cahyani; Azhar Huwaiza Fathoni; Jihan Salsabilah (Jurnal Kabar Masyarakat, 2024)
Srimukti Village has great potential in the development of Micro, Small, and Medium Enterprises (MSMEs). This can be seen from the fact that most of the areas of Srimukti Village are rice fields that are used as a source of income. However, based on the results of observations and data obtained, there are still many MSME actors in Srimukti Village who do not have adequate knowledge and skills in managing their business finances. This study describes the implementation of the Community Service Program (KKN) with the theme "Building Developing and Advanced Community Empowerment Through MSME Financial Bookkeeping Training in Srimukti Village". This program aims to improve the knowledge and skills of MSME actors in managing their business finances, so that they can improve the development and progress of MSMEs in the village, as well as increase community income and contribute to improving the village economy. The research techniques used were observation, interviews, and documentation. The results of the study showed that the MSME financial bookkeeping training program to build developing and advanced community empowerment in Srimukti Village has been successfully implemented and has shown positive results. This program has increased the knowledge and skills of MSME actors in managing their business finances, so that it can improve the development and progress of MSMEs in the village, as well as increase community income and contribute to improving the village economy.